EFEKTIVITAS KAYU APU DALAM PENURUNAN KADAR COD DAN PH PADA LIMBAH CAIR LAUNDRY DI BIRU-BIRU KABUPATEN DELI SERDANG TAHUN 2025 - MARBUN, VIKTOR EDYWARD; Sari, Lina; Sembiring, Johannes (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2025)
The laundry business is growing rapidly in Indonesia, but the management of liquid waste from laundry activities is still inadequate and has the potential to pollute the environment. This study aimed to determine the effectiveness of pumice wood (Pistia stratiotes) in reducing Chemical Oxygen Demand (COD) levels and Power of Hydrogen (pH) values in laundry wastewater in Biru-Biru District, Deli Serdang Regency. This study was a quantitative descriptive study with contact times varying from 2, 4, and 6 days. Twenty liters of laundry wastewater were used as samples, and water quality was measured before and after treatment using a spectrophotometer and pH meter. The results of the study showed that COD levels decreased significantly from 585 mg/L (before treatment) to 194 mg/L on the 6th day, or by 66.84%. The pH value also decreased from 9.5 to 8.0, or by 15.79%, which meets the liquid waste quality standards (6.0–9.0). The effectiveness of pumice wood in the phytoremediation process is due to its ability to absorb organic matter and support the activity of microorganisms around its roots which accelerates the pollutant degradation process. In conclusion, Pistia stratiotes has been proven to be effective, environmentally friendly, and low-cost in reducing COD levels and stabilizing pH in laundry wastewater. It is recommended for small-scale laundry businesses as an alternative simple and sustainable waste processing system.